Mono-and Triphenyltin Derivatives of N-(2-Hydroxy Methyl Substituted Benzyl) Valines - Ballabh Mishra, Shashi; P. Pande, Ashutosh; Nagarkoti, Sangita; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Mono- and triphenyltin derivatives of N-(2-hydroxy methyl substituted benzyl) valines have been prepared by alcoholysis reaction. The compounds were obtained as coloured solids in each case and amongst them those containing isopropoxy group were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analysis, as well as by spectral measurements.